(untitled) (Interdisciplinary Research in Education, 2024)
This study examines the experiences of sexual harassment among female students at higher educations in Kathmandu valley under Tribhuvan University, Nepal. The study employs a focus group discussions and in-depth interviews with female students across various higher educational institutes. Findings reveal that sexual harassment is pervasive, occurring both on and off-campus situation, and manifests in physical, verbal, and non-verbal forms. Participants emphasized the need for strict laws, effective enforcement, and increased societal awareness will be effective to mitigate these issues. The research finding elaborated the importance of female empowerment and systemic change to combat sexual harassment in academic and public spaces in Nepal.